Methods of economic efficiency assessment of the operation stage of the aviation engines life cycle - Tatyana Rogulenko; Oleg Smolyakov (Управление)
The relevance of the evaluation of the technical and economic efficiency of aircraft engines and one of its main indicators – direct operating costs has been noted in the article. Their place in ensuring the competitiveness of aircraft in the relevant sectors of the market has been established. One of the main indicators of the efficiency of aviation equipment is its technical and economic evaluation. Tough competition, existing, at present between foreign players in the aircraft industry and difficulties of maintaining their positions to Russian aircraft manufacturers have been designated. The features of existing foreign and domestic methods and approaches to the economic evaluation of aircraft engines have been noted, and their comparative analysis has been carried out. Problematic issues when considering the efficiency of the aircraft as a whole and the difficulties of technical and economic assessment of the aircraft engine as a subsystem of the aircraft have been revealed. The need has been indicated to take into account the condition under which, if we consider the aircraft as a whole, the efficiency of its operation is mainly determined by the perfection of the engines of the power plant. It has been noticed, that the engine can act on the market as an independent product, having a market price. But, at the same time, it is necessary to take into account that the aircraft engine is a subsystem of the aircraft, therefore, it follows to carry out its technical and economic assessment, taking into account, if possible, the characteristics of the aircraft and the characteristics of its operation, which is a difficult task and this is a necessary procedure in case of economic evaluation. The need for careful selection of performance indicators, contributing to a reliable assessment of the competitiveness of the proposed product has been designated. At the same time, it is necessary to adhere to a certain framework, namely when comparing competing engines, the technical and economic evaluation of aircraft engines should be carried out under the same conditions regarding the operation and maintenance of the aircraft as a whole. Moreover, engines should have similar indicators: dimensionality, installation on a plane of the same class, etc.